Haloduracin α Binds the Peptidoglycan Precursor Lipid II with 2:1 Stoichiometry - Oman, Trent J. (American Chemical Society, 2011)
[Image: see text] The two-peptide lantibiotic haloduracin is composed of two post-translationally modified polycyclic peptides that synergistically act on Gram-positive bacteria. We show here that Halα inhibits the transglycosylation reaction catalyzed by PBP1b by binding in a 2:1 stoichiometry to its substrate lipid II. Halβ and the mutant Halα-E22Q were not able to inhibit this step in peptidoglycan biosynthesis, but Halα with its leader peptide still attached was a potent inhibitor. Combined with previous findings, the data support a model in which a 1:2:2 lipid II:Halα:Halβ complex inhibits cell wall biosynthesis and mediates pore formation, resulting in loss of membrane potential and potassium efflux.